Web Based Application Wet Cake Snack Product Distribution Using Concept Business To Business To Consumer - Mansur, Mansur; Mawardah, Dinda Nurul (Publisher: Fakultas Ilmu Komputer, Institution: Universitas Lancang Kuning, 2022)
Business To Business To Customers is part of E-Commerce which is a process of buying and selling transactions and distribution to consumers. Distribution of wet cakes from producers on Jl. Panglima Minal Senggoro is still manual by recording and monitoring products that run out from partners. Distribution from producers to retailers uses a profit-sharing system that has been agreed upon by both parties. The design of this system is designed using the Waterfall method and the Codeigniter Framework (CI) as well as with the design of the E-commerce Framework, namely B2B2C which produces information about cake manufacturers, knows the available products, and also helps producers in recapitulating sales to partners. The features in this system are Approval in user registration, the input of cake products, selection of payment methods, uploading proof of payment, updating of remaining products on the partner side, and dynamic reviews and ratings. So that producers can compete with other wet cake.